Influence of initial performance level and tactical position on the aerobic fitness in soccer players after preseason period - Los Arcos, A.; Castillo, D.; Martinez-Santos, R. (Science and Medicine in Football, 2018)
Objectives: The purpose of this study was to examine the changes in aerobic fitness in young elite Spanish soccer players after the pre-competitive period over 12 seasons depending on the initial performance level and the tactical position. Methods: One hundred and thirty players belonging to the same reserve team of a Spanish La Liga Club participated in this study. Aerobic fitness capacity (the velocity associated with a blood lactate concentration [La]b of 3 mmol l-1 [V3]) was assessed in each season at the start of the preseason (i.e. July), Test 1 (T1), and the start of the competitive period (i.e. September), Test 2 (T2), from 1998 to 2013 season. Results: Taking all seasons together a most likely small improvement (effect size (ES) = 0.52; ±0.09) was found in V3 after preseason, but this varied from trivial to moderate among the seasons. A most likely large improvement was found for the players with lower V3 values in T1 (ES = 1.68; ±0.38) while a likely small enhancement was assigned to the group with higher V3 values (ES = 0.53; ±0.42). Conclusions: Technical staff should be cautious about affirming an improvement in aerobic fitness after preseason.